Pengaruh Disiplin Kerja dan Loyalitas Kerja Terhadap Kinerja Karyawan - Tetty Rahmiati Harahap (TIN: Terapan Informatika Nusantara, 2023)
The purpose of this research is to determine the influence of work discipline on employee performance, the influence of work loyalty on employee performance, and the joint influence of work discipline and work loyalty on employee performance at LPP TVRI North Sumatra. The methodology used in this research is quantitative descriptive. Data was collected through the use of questionnaires and direct observation. The research population was 119 employees, with a sample of 92 employees selected using the simple random sampling method. The results of the research show that in the relationship between work discipline (X1) and employee performance (Y), the calculated t value is 0.376, which is smaller than the t table value (1.990), with a significance of 0.708 which is greater than the significance. level 0.05. This means that work discipline (X1) has no significant effect on employee performance (Y). Likewise, in the relationship between work loyalty (X2) and employee performance (Y), the calculated t value of -0.457 is also smaller than the t table value (1.990), with a significance of 0.649 which is greater than the significance level. of 0.05. This shows that work loyalty (X2) does not have a significant effect on employee performance (Y). The results of the F test of the simultaneous influence of work discipline (X1) and work loyalty (X2) on employee performance (Y), show that the calculated F value is 0.115 smaller than the F table value (3.10), and the significance probability value is 0.892 greater than significance level of 0.05. This shows that together work discipline (X1) and work loyalty (X2) do not have a significant influence on employee performance (Y).